Building Good Communication with Children for Family Harmony - Rahma Rahma; Amanda Anatasya (Socrates: Journal of Education, Philosophy and Psychology, 2025)
Good communication between parents and children is the primary foundation for building family harmony. This article discusses the importance of positive communication in family relationships, factors influencing its success, and effective strategies for everyday life. This study employs a descriptive method with a qualitative approach to identify family experiences in fostering communication. The findings reveal that open communication, empathy, and active involvement in children's lives contribute to creating harmonious family relationships. Therefore, effective communication strategies are the key to successful family relationships.